STUDI KOMPARATIF EFEKTIVITAS PENGELOLAAN PAJAK BUMI DAN BANGUNAN (PBB) SEBELUM DAN SESUDAH BERLAKUNYA UNDANG-UNDANG NO. 28 TAHUN 2009 PADA KABUPATEN KEDIRI - RAHMATIKA, ALVY (Jurnal Akuntansi AKUNESA, 2015)
One of the government's efforts in promoting the region and increase local revenue with inaugurate Undang-Undang Nomor 28 Tahun 2009 Tentang Pajak Daerah dan Retribusi Daerah. With the existence of these laws, there is delegation of authority as well as the acceptance of PBB to local governments. According to Direktorat Jenderal pajak (DJP), when PBB is managed by central government, local governments acquire part of PBB amounted to only 64.8%. With the delegation of authority is the local government can manage PBB equal to 100% of its acceptance..This policy conducted begin no later than January 1,2014. Kabupaten Kediri implement this policy in 2013. During this time the effectiveness of the PBB reception is always above 100%, which means that the realization of PBB always through the target.Keyword: UU No. 28 Tahun 2009, PBB